2009
DOI: 10.2143/ac.64.6.2044737
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disturbances after cardiac surgery with or without elevated S100B levels

Abstract: Cardiac surgery affects a patient's sleep characteristics. Patients with elevated S100B values have more sleep disturbances after cardiac surgery than patients with normal S100B values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…The sleep time tended to normalize after one month but could be affected as long as 6 months postoperatively. Sleep efficiency was measured in 7 of the 9 studies [25][26][27]31,32,35,36 and showed the same tendency as total sleep time, with a reduction in the first postoperative week and normalization one month postoperatively. An age effect was shown, where people < 60 years returned to preoperative values after one month, but people > 60 years needed 2 months to return to preoperative values.…”
Section: Cardiac Surgerymentioning
confidence: 87%
See 4 more Smart Citations
“…The sleep time tended to normalize after one month but could be affected as long as 6 months postoperatively. Sleep efficiency was measured in 7 of the 9 studies [25][26][27]31,32,35,36 and showed the same tendency as total sleep time, with a reduction in the first postoperative week and normalization one month postoperatively. An age effect was shown, where people < 60 years returned to preoperative values after one month, but people > 60 years needed 2 months to return to preoperative values.…”
Section: Cardiac Surgerymentioning
confidence: 87%
“…Of the 24 studies in which actigraphy was used to assess sleep, 9 studies were in patients undergoing cardiac surgery, [25][26][27],31-36 6 general surgery, 2,[22][23][24]37,38 5 outpatient surgery, 39-43 2 breast surgery, 44,45 and the last 2 studies involved gynecological/obstetric surgery. 46,47 Three studies were randomized clinical trials.…”
Section: Sleepmentioning
confidence: 99%
See 3 more Smart Citations